PENGARUH KOMPETENSI PEGAWAI DAN DAYA DUKUNG FASILITAS PERPUSTAKAAN TERHADAP KUALITAS LAYANAN PADA PERPUSTAKAAN UNIVERSITAS SANG BUMI RUWA JURAI BANDAR LAMPUNG - . Nesya (e-JKPP, 2017)
Universities library as institutions engaged in the field of information services have a very important role in building the nation's intelligence. Problems identified in this study is still their users have complained less of a response of employees in providing services to users. Library employees in performing their duties is not concerned with the process of service performed and only concerned with the end result. In carrying out the tasks they are employees who do not have the understanding of competence in providing information to the user about the location and name of the author of the book that makes the difficulty in finding a book. In addition, the collection of books as library facilities available are still not in accordance with user needs. Collection of reading books published many years old and less up to date.The purpose of this study partially or simultaneously is to analyze and determine the effect of employee competence and resources to support the service quality library facilities at the University Library of Sang Bumi Ruwa Jurai Bandar Lampung.The method used in this study is a survey method, a case study at the Sang Bumi Ruwa Jurai University student, which is done by distributing questionnaires in the study subjects. Analysis of the data used is quantitative analysis.Keyword : Employee competency, Support facilities, Quality of service